2019
DOI: 10.21203/rs.2.14196/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of Type I Interferon Signaling abrogates Early Mycobacterium bovis Infection

Abstract: Background: Mycobacterium bovis (M. bovis) is the central causative agent of bovine tuberculosis; however, it also caused serious infection in human beings. Type I IFNs is a key factor in reducing viral multiplication and modulate host immune defense against viral infection. However, the regulatory pathways of type I IFN signaling during Mycobactrium bovis (M. bovis) infection are not yet fully explored. Here, we investigate the role of type I IFN signaling on the pathogenesis of M. bovis infection in mice. Me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Not only does the death of infected macrophages release the pathogen to infect other cells, but the release of host cell contents may trigger tissue-damaging inflammation. Absence of Ifnar1 in 129S2 mice markedly reduced migration of inflammatory monocytes and neutrophils to the lungs ( Dorhoi et al, 2014 ), and prophylaxis with anti-IFNAR1 mAb protected mice subsequently infected with virulent Mycobacterium bovis ( Wang et al, 2019 ). Type I IFNs impaired the activation of macrophages by type II IFN (IFN-γ; Yoshida et al, 1988 ), which is essential for controlling TB in mice ( Cooper et al, 1993 ; Flynn et al, 1993 ) and people ( Jouanguy et al, 1996 ; Jouanguy et al, 1997 ), and this was also seen in the context of infection with Listeria monocytogenes ( Rayamajhi et al, 2010 ) and Mycobacterium leprae ( Teles et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Not only does the death of infected macrophages release the pathogen to infect other cells, but the release of host cell contents may trigger tissue-damaging inflammation. Absence of Ifnar1 in 129S2 mice markedly reduced migration of inflammatory monocytes and neutrophils to the lungs ( Dorhoi et al, 2014 ), and prophylaxis with anti-IFNAR1 mAb protected mice subsequently infected with virulent Mycobacterium bovis ( Wang et al, 2019 ). Type I IFNs impaired the activation of macrophages by type II IFN (IFN-γ; Yoshida et al, 1988 ), which is essential for controlling TB in mice ( Cooper et al, 1993 ; Flynn et al, 1993 ) and people ( Jouanguy et al, 1996 ; Jouanguy et al, 1997 ), and this was also seen in the context of infection with Listeria monocytogenes ( Rayamajhi et al, 2010 ) and Mycobacterium leprae ( Teles et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…A reduction in neutrophil recruitment was observed in vivo along with reduced IL-10 and IL-6 and increased IFN-γ and IL-1β. In vitro, macrophages treated with αIFNAR1 induced decreased levels of M2 markers, such as Arg1, Ym1, and Mrc1, and increased expression of M1 markers such as Nos2 and Ifng, suggesting that type I IFN signaling mediates macrophage polarization toward an anti-inflammatory profile during M. bovis infection [55]. Another study found that macrophages deficient in either IFNAR or STAT exhibited increased viability compared with WT cells after infection with M. tuberculosis [56].…”
Section: The Roles Of Type I Ifns In Bacterial Infectionsmentioning
confidence: 99%
“…M. tuberculosis was also shown to inhibit autocrine type I IFN signaling (by 50-60%) via reduced phosphorylation of the IFNAR-associated protein kinases JAK1 and TYK2, leading to reduced phosphorylation of STAT1 and STAT2 [54], suggesting that the type I IFN response could be detrimental to the pathogen but this is a good example of how in vitro does not always correlate to in vivo. Murine models with the bovine turbercule bacilli, Mycobacterium bovis, are protected against infection when IFNAR is neutralized [55]. Both cellular and immune signaling differences were noted.…”
Section: The Roles Of Type I Ifns In Bacterial Infectionsmentioning
confidence: 99%
“…Relatively little is known regarding neutrophil killing of mycobacteria, as the host immune response has been considered primarily a by guest on October 16, 2022 http://www.jimmunol.org/ Downloaded from macrophage-and adaptive immunity-driven process (21)(22)(23). However, abundant neutrophils are observed at sites of infection (1,24,25), and evidence suggests they play a role in clearance of mycobacterial infections, although they may also aid survival within the host (26)(27)(28)(29)(30).…”
mentioning
confidence: 99%